2005
DOI: 10.1161/01.atv.0000183887.76087.6a
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Arterial Responses and Inflammatory Markers in Afro-Caribbean and Caucasian Subjects

Abstract: Objective-Small vessel disease is more common in Afro-Caribbeans than Caucasians. We investigated underlying differences in metabolic, inflammatory, and vascular responses that may predispose Afro-Caribbeans to small vessel pathology. Methods and Results-Seventy-eight Afro-Caribbeans aged 35-75 years, with no vascular disease or medications, were compared with 82 matched Caucasians for metabolic variables, fasting insulin, interleukin 6, tumor necrosis factor (TNF) ␣, and cytoplasmic repressor protein levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 48 publications
6
38
0
Order By: Relevance
“…19 Endothelial function in healthy blacks is attenuated relative to healthy whites. 24 In the current study, highest homocysteine levels were found in SVD patients who also had confluent leukoaraiosis.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…19 Endothelial function in healthy blacks is attenuated relative to healthy whites. 24 In the current study, highest homocysteine levels were found in SVD patients who also had confluent leukoaraiosis.…”
Section: Discussionsupporting
confidence: 46%
“…22,23 Attenuated endothelial function has been reported in healthy stroke-free black volunteers, relative to whites. 24 Homocysteine has been identified as a risk factor for ischemic stroke in whites but not black Americans in a prospective study where stroke subtyping was not performed. 25 Whether elevated homocysteine is particularly associated with the SVD subtype in black populations is uncertain.…”
mentioning
confidence: 99%
“…A genetic basis of the latter has been suggested, 9 and impaired endothelial function has been reported in black individuals without stroke. 24 The differing distribution in atherosclerotic disease between the 2 populations was striking. Consistent with some but not all previous studies, we found that large artery disease was almost twice as common among white as black individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, African-Caribbean individuals have accelerated arterial aging, increased aortic stiffness and greater carotid intima thickness when compared with European and Asian populations. [113][114][115] This indicates the likely presence of genetic loci controlling multiple aspects of vessel aging. Similarly, age-related artery stiffness is more pronounced in women and is independent of the menopause, reflecting intrinsic differences in arterial properties between sexes.…”
Section: Systemic Causesmentioning
confidence: 96%